Direct Teacher Corrective Feedback in EFL Writing Class at Higher Education: What Students Perceive - Sabarun, Sabarun (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2020)
The study is aimed at describing the students’ perception of direct teacher corrective feedback in a foreign language writing class. It is descriptive quantitative research, employing questionnaires and observation as research instruments, which was conducted with 20 students of the fourth semester English department students of Palangka Raya State Islamic Institute of 2018/ 2019 academic year. The findings revealed that, firstly, in terms of the perception of students’ attitudes toward direct teacher corrective feedback, 75 percent of participants felt that they agreed to receive direct teacher corrective feedback on language form, content, and organization. Their preference for the area of corrective feedback in language forms was 85 percent while the organization was 65 percent. Secondly, dealing with the students’ perception on direct teacher feedback, 90 percent of students argued that they felt satisfied when they got direct teacher feedback. 85 percent of students perceived that their teacher’s feedback helped them improve their writing, and 90 percent of them realized that their teacher’s feedback made them feel confident in producing a better draft. Finally, most students responded that they appreciated the teacher’s feedback. In addition, the students believed that direct teacher feedback improved writing especially on grammar accuracy and organization.